Research on English Teaching Policies for Public Schools: From Past to Future Paths (2020)
The following paper introduces research studies and publications that could broaden English language teachers and scholars’ understanding about policies for the teaching of English, targeted at public primary schools in various countries of the world. This article also explains how these policies have been addressed in these institutions depending on their needs, the contexts, and the perspectives of teachers, administrators, and stakeholders.